REDUCING CHEMICAL FERTILIZER IN SWEET POTATO CULTIVATION BY USING MIXED BIOFERTILIZER - & et al., Hindersah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Biofertilizer enable to improve nutrient cycle in soil and induce plant growth and production, but sweet potatoes farmers in Indonesia are still use only chemical fertilizer as a source of plant nutrient. The objectives of this experiment were to evaluate the effect of different doses of consortium biofertilizer to reduce chemical fertilizer dose; and maintain yield and sweetness of two sweet potato varieties. The experimental design was completely randomized block design which tested six combinations of different chemical fertilizer and biofertilizer doses. Analysis of variance was performed to determine any significant differences between the means of treatments. The results showed that the response of both sweet potatoes varieties on combined application of chemical and bio fertilizer was differ. All treatments did not change tuber number and weight of sweet potato var. Awachy-1 but increased those of var. Rancing. Application of diazotrophic bacteria (Azotobacter, Azospirillum and Acinetobacter) mixed with phosphate solubilizing microbes (Pseudomonas and Penicillium) with reduced fertilizer doses up to 75% did not alter soil available nitrogen and phosphorous. Despite different fertilizer rates, tubers number of both sweet potato varieties in individual plot was similar. Yield did not change due to reduction of fertilizer dose up to 75% when biofertilizer was applied. However, yield was potentially decreased when chemical fertilizer was only 50%. All fertilizer treatments did not change the sweetness of tuber which indicated by constant brix. Research suggested that biofertilizer might substitute 25% of chemical fertilizer to obtain the same yield and quality of tuber, and maintain the availability soil nitrogen and phosphorous.